Boldness and Prudence. The Moderate Approach to Morality and Religious Tolerance: 1844-1847 - Santillán, Gustavo (Anuario de Historia de América Latina, 2025)
The article explores the political language of the moderate group in Mexico between the fall of Antonio López de Santa Anna (1844) and the end of the war with the United States (1847) on religious elements such as Christian morality and cult tolerance. Based on an investigation in brochures, newspapers and official documents, it offers a panorama where audacity and prudence converge, in a mixture equidistant from doubt or indeterminacy. Thus, moderates such as Luis de la Rosa and José María Lafragua were the first to propose from governmental instances a certain tolerance of cults and a perspective of ethical plurality. The text proposes a reassessment of moderate thought as an option for change in the face of Juarista reformism.
Keywords: Morality; Moderates; Tolerance; Liberalism; Luis de la Rosa; José María Lafragua; Act of Reforms.